The Influence of Village Fund Allocation and Community Empowerment on Improving Community Welfare in Mattampapole Village - Lisnayanti; Abdul Muthalib; Faidul Adziem (GoodWill, 2026)
This research aims to find out, 1) the influence of village fund allocation on improving the welfare of the people of Mattampapole Village. 2) The influence of community empowerment has an impact on improving the welfare of the people of Mattampapole Village. 3) the influence of village fund allocation and community empowerment on improving community welfare in Mattampapole Village. This type of research is quantitative research. The population in this study was the community in Mattampapole Village with a total of 929 people. In determining the size of the sample members from each member of the population, it can be determined based on the formula for determining the size of the sample members using the Slovin formula and a sample of 90 respondents is obtained. Data collection techniques in this research consist of questionnaires and documentation. The data analysis technique used is descriptive and inferential statistics with the help of SPSS 25. The results of the research show that: 1) The effect of village fund allocation on increasing community welfare in Mattampapole Village was obtained by t count of 2.656 and t table of 1.987 with a significant value of 0.001 < 0.05. This means that t count is 2.656 > t table 1.987 with a significance value of 0.001 < 0.05, in the medium category with a percentage of 49.5%. 2) The positive and significant influence of community empowerment on improving community welfare in Mattampapole Village was obtained by t count of 2.656 and t table of 1.987 with a significant value of 0.003 < 0.05. This means that t count is 2.656 > t table 1.987 with a significance value of 0.003 < 0.05, in the medium category with a percentage of 50.3%. 3) The influence of village fund allocation and community empowerment on improving community welfare in Mattampapole Village is 51.9%.